2017
DOI: 10.3390/catal7080226
|View full text |Cite
|
Sign up to set email alerts
|

Renewable Hydrogen from Ethanol Reforming over CeO2-SiO2 Based Catalysts

Abstract: Abstract:In this research, a bimetallic Pt-Ni/CeO 2 -SiO 2 catalyst, synthetized via wet impregnation, was successfully employed for the oxidative steam reforming of ethanol between 300 and 600 • C. The reaction performance of the Pt-Ni catalyst was investigated and compared with the Ni/CeO 2 -SiO 2 , Pt/CeO 2 -SiO 2 as well as CeO 2 -SiO 2 sample. The bimetallic catalyst displayed the best results in terms of hydrogen yield and by-products selectivity, thus highlighting the crucial role of active species (Pt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 69 publications
0
16
0
Order By: Relevance
“…The Pd/CeO2 and Pd/SiO2 samples exhibited positive peak regions at approximately 300 and 700 °C, and 750 °C, respectively. These positive peaks indicated that bulk PdOx species were reduced to Pd 0 or hydrogen spillover [15,16]. To verify the reduction properties of the Pd catalysts, H 2 -TPR analysis was performed, and the results are shown in Figure 4.…”
Section: Characterization Of Supports and Pd Catalystsmentioning
confidence: 99%
“…The Pd/CeO2 and Pd/SiO2 samples exhibited positive peak regions at approximately 300 and 700 °C, and 750 °C, respectively. These positive peaks indicated that bulk PdOx species were reduced to Pd 0 or hydrogen spillover [15,16]. To verify the reduction properties of the Pd catalysts, H 2 -TPR analysis was performed, and the results are shown in Figure 4.…”
Section: Characterization Of Supports and Pd Catalystsmentioning
confidence: 99%
“…Some bimetallic or multi-component catalysts have higher CH 4 conversion rates compared to their single-metal catalysts-for example, Pd/Al 2 O 3 modified with NiO and MgO [16], Rh-LaMnO 3 /Al 2 O 3 [17], Ce-Cr/γ-Al 2 O 3 [18], Ni-Cr/yttria-doped Ce [19], Rh-LaMnO 3 honeycomb [20], and Au-Pd/nanohybrid 3D macroporous La 0.6 Sr 0.4 MnO 3 [21,22]. In the presence of two or more main metal components, the reported activity of these catalysts was mostly enhanced due to a synergistic catalytic effect and/or the second metal added enhanced dispersion of the main active species [23].…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have made an effort to synthesize compatible catalysts for use in diesel reforming [8,9]. Ethanol reforming for hydrogen production was conducted over several catalysts (Ni/CeO 2 -SiO 2 , Pt/CeO 2 -SiO 2 , Pt-Ni/CeO 2 -SiO 2 , and Ni/CeO 2 ) [10,11]. Precious metal-based (Pt, Pd, Rh, and Ru) catalysts exhibit better resistance to carbon deposition and sulfur poisoning than Ni-based catalysts.…”
Section: Introductionmentioning
confidence: 99%